Branding in Asia the creation, development, and management of Asian brands for the global market - Temporal, Paul (John Wiley & Sons (Asia) Pte Ltd, 2000)
"In this book, Asia's leading brand architect explains the fundamentals of branding and shows how companies can use them to achieve outstanding performance." "Packed with illustrative examples, techniques, advice and exercises, this book will help any company, regardless of size, to: build a strong brand image; create a unique and sustainable competitive advantage; develop solid plans for international expansion; access and penetrate new markets; attract and retain customers; motivate employees; gain global recognition; and establish permanent growth in profitability and asset value."--Jacket.